Analisa Laporan Keuangan sebagai Alat untuk Menilai Kinerja pada KSU “Kencana Makmur” Cabang Laren - Firman Nur Aprilianto; Biyati Ahwarumi; Anisatul Mahmudah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2019)
KSU Kencana Makmur Laren Branch needs to analyze financial statements in order to know the company's financial picture from period to period. Qualitative research. The research formulation consists of: 1) How is the financial reporting system at KSU